2020
DOI: 10.1016/j.tbs.2020.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Eliciting preferences of TNC users and drivers: Evidence from the United States

Abstract: Transportation Network Companies (TNCs) are changing the transportation ecosystem, but microdecisions of drivers and users need to be better understood to assess the system-level impacts of TNCs. In this regard, we contribute to the literature by estimating a) individuals' preferences of being a rider, a driver, or a non-user of TNC services; b) preferences of ridehailing users for ridepooling; c) TNC drivers' choice to switch to vehicles with better fuel economy, and also d) the drivers' decision to buy, rent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 30 publications
1
21
0
Order By: Relevance
“…They found that younger and unmarried individuals reported significantly higher rates of pooling; whereas, there were no statistically significant differences by gender or household income bracket. Other studies of TNC users in the metropolitan U.S. and Dallas, TX corroborate that the use of pooling decreases with the age of the TNC user (Lavieri & Bhat, 2019;Bansal, et al, 2019), but some have found that this relationship between age and propensity for pooling varies by other sociodemographic characteristics such as education level and gender (Bansal, et al, 2019). Studies have also found mixed results when it comes to the relationship between household car ownership and preference of a TNC user to pool, with some noting a positive (Sarriera, et al, 2017) and others a negative relation (Bansal, et al, 2019).…”
Section: Who Uses Tnc Services (Both Exclusive and Pooled)?mentioning
confidence: 77%
See 2 more Smart Citations
“…They found that younger and unmarried individuals reported significantly higher rates of pooling; whereas, there were no statistically significant differences by gender or household income bracket. Other studies of TNC users in the metropolitan U.S. and Dallas, TX corroborate that the use of pooling decreases with the age of the TNC user (Lavieri & Bhat, 2019;Bansal, et al, 2019), but some have found that this relationship between age and propensity for pooling varies by other sociodemographic characteristics such as education level and gender (Bansal, et al, 2019). Studies have also found mixed results when it comes to the relationship between household car ownership and preference of a TNC user to pool, with some noting a positive (Sarriera, et al, 2017) and others a negative relation (Bansal, et al, 2019).…”
Section: Who Uses Tnc Services (Both Exclusive and Pooled)?mentioning
confidence: 77%
“…Finally, a number of studies have compared car ownership between users and non-users of TNC services. Nationally, not owning a car is highly related to TNC use (Schaller, 2018;Smith, 2016) and as many as 10% of TNC users report postponing the purchase of a new car (Bansal, et al, 2019, Hampshire, et al, 2018. In San Francisco and Boston, the proportion of TNC users that come from zero-car households was found to be much higher than the metropolitan region (Rayle, et al, 2016, Gehrke, Felix, & Reardon, 2018.…”
Section: Who Uses Tnc Services (Both Exclusive and Pooled)?mentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, the service could be affordable for a broader mass of travelers-whereas ridehailing is currently mainly used by young, well-educated urbanites (cf. [16,[25][26][27]. Spurlock et al [28] already provide evidence that "low-to middle-income people [...] adopted pooled ride-hailing" [28] (p. 39), whereas non-pooled ride-hailing is rather used by those with higher income.…”
Section: Introductionmentioning
confidence: 99%
“…Second, it is of particular interest to explore how these two groups (transit users and auto users) might have different attitudes and preferences toward mobility options, and how their attitudes may affect their mode choice toward ridesourcing options. While the literature has indicated that psychological constructs, such as attitudes, perceptions, and desires, have considerable impacts on individuals' mode choice behavior, few papers have investigated the impacts of attitudes on travelers' mode choice in the context of ridesourcing (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26).…”
mentioning
confidence: 99%